2022
DOI: 10.3390/biomedicines10102528
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Nivolumab and Ipilimumab Combined Immunotherapy in the Treatment of Metastatic Melanoma in Poland: A Multicenter Experience

Abstract: Nivolumab and ipilimumab combination became the first-line standard in advanced melanoma. We assessed its efficacy in a real-life study in Poland. In a one-year follow-up, we evaluated the medical records of 50 melanoma patients treated with that modality in five oncology centers. We recorded therapy outcomes and adverse events (AEs) after 3 and 12 months of therapy. At the first checkpoint, the disease control rate (DCR) was recorded in 58% (n = 29) of patients, but the same number of patients (n = 29, 58%) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…There is a rationale for considering irAEs as a predictive factor for oncological responses. To date, several studies have revealed a correlation between irAEs and better survival [ 79 , 91 , 92 , 93 ]. In our real-life report, melanoma patients treated with combined immunotherapy who experienced irAEs had an 80% lower risk of death (hazard ratio (HR) 0.2, 95% CI 0.07–0.57, p = 0.001) and disease progression (HR 0.2, 95% CI 0.09–0.47, p < 0.0001) [ 93 ].…”
Section: Surprisingly Patients Who Develop Immune-related Adverse Eve...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a rationale for considering irAEs as a predictive factor for oncological responses. To date, several studies have revealed a correlation between irAEs and better survival [ 79 , 91 , 92 , 93 ]. In our real-life report, melanoma patients treated with combined immunotherapy who experienced irAEs had an 80% lower risk of death (hazard ratio (HR) 0.2, 95% CI 0.07–0.57, p = 0.001) and disease progression (HR 0.2, 95% CI 0.09–0.47, p < 0.0001) [ 93 ].…”
Section: Surprisingly Patients Who Develop Immune-related Adverse Eve...mentioning
confidence: 99%
“…To date, several studies have revealed a correlation between irAEs and better survival [ 79 , 91 , 92 , 93 ]. In our real-life report, melanoma patients treated with combined immunotherapy who experienced irAEs had an 80% lower risk of death (hazard ratio (HR) 0.2, 95% CI 0.07–0.57, p = 0.001) and disease progression (HR 0.2, 95% CI 0.09–0.47, p < 0.0001) [ 93 ]. In another major study of 1747 patients with metastatic or locally advanced urothelial cancer treated with anti-PD-1/PD-L1 antibodies, irAEs were reported in 28% of responders vs. 12% of non-responders [ 92 ].…”
Section: Surprisingly Patients Who Develop Immune-related Adverse Eve...mentioning
confidence: 99%